Trabalho, privação, delito e experiência portenha - Kessler, Gabriel (2010)
This article is based on my research with people, generally young, responsible for crimes against property over recent decades in Buenos Aires. The analysis emphasizes the different connections between crime, work, poverty and urban experience formed over this time period. I look to show that, far from being a "criminal underworld" with its own logic, the transformations in the illegalities under study are generally conditioned by two factors: transformations in the labour market and changes in the cultural experience of poverty, whose meaning is linked to the equally mutating place of consumption. Finally the city, the place where everything unfolds, is transformed at the same time as the urban experience of the subjects alters and interferes in the illegalities under study.